If (f + g)(x) = 3×2 + 2x – 1 and g(x) = 2x – 2, what is f(x)? A. 3×2 + 1 B. 3×2 – 1 C. 3×2 + 4

Question

If (f + g)(x) = 3×2 + 2x – 1 and g(x) = 2x – 2, what is f(x)?
A.
3×2 + 1
B.
3×2 – 1
C.
3×2 + 4
D.
3×2 – 4
E.
x2 – 2

in progress 0
Piper 2 weeks 2021-09-08T18:54:59+00:00 1 Answer 0

Answers ( )

    0
    2021-09-08T18:56:38+00:00

    Answer:

    the A is right

    Step-by-step explanation:

    We have (f+g)(x) = f(x) +g(x)

    So f(x) + g(x) = 3x^2 + 2x – 1 and we know g(x) = 2x -2

    or f(x) + 2x-2 = 3x^2 + 2x – 1

    f(x) = 3x^2 + 2x – 1 – ( 2x -2)

    f(x) = 3x^2 + 2x – 1 – 2x +2 \

    finally

    f(x) = 3x^2 + 1, and the A is right.

    Have a good day

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )